"Conflicts of interests" within and between elite assemblages in the legal production of space: Indigenous cultural heritage preservation and the Dakota Access Pipeline. Issue 1 (15th November 2021) - Horowitz, Leah S.
Abstract: This paper represents a "studying‐up" of the controversy over federal regulatory processes regarding protection of Lakota and Dakota cultural heritage in permitting the Dakota Access Pipeline (DAPL). To analyse this controversy, I engage with interest‐convergence theory, a component of Critical Race Theory, alongside a critique of its arguably simplistic definition of "white interests." Agreeing that we need a finer‐grained understanding of elite interests as multiple, conflicting, and not always based purely in material self‐interest, I argue that interests should be understood as nonhuman components of elite assemblages, shaped by both emotions and societal ideologies yet constrained by – and in conflict with – top‐down, ideology‐driven missions and institutional cultural norms, as well as pressure from other assemblages. I use this framework to examine conflicts within and among various elite assemblages' interests surrounding Lakota and Dakota cultural heritage. The US Army Corps of Engineers' emotion‐ and ideology‐driven interests in demonstrating sensitivity to tribes' concerns were constrained by their mission‐driven interests in accomplishing duties in a timely manner. These interests, in turn, conflicted with concerns (or lack thereof) manifested by other federal entities (Advisory Council on Historic Preservation, DC District Court) about DAPL's impacts on cultural heritage, and with the company's and federal government's financial interests in pressuring USACE to enable completion of the pipeline's construction. I unpack power differentials and dynamics among these various groups, as realised through particular interpretations and implementations of relevant legislation. I suggest that examining such "conflicts of interests" within and between elite assemblages, within the legal production of space, can elucidate controversies over industrial expansion's socio‐environmental threats. Abstract : This paper represents a "studying‐up" of the controversy over federal regulatory processes regarding protection of Lakota and Dakota cultural heritage in permitting the Dakota Access Pipeline (DAPL). I argue that interests should be understood as components of elite assemblages, shaped by both emotions and societal ideologies yet constrained by – and in conflict with – top‐down, ideology‐driven missions and institutional cultural norms, as well as pressure from other assemblages. I use this framework to examine conflicts within and among various elite assemblages' interests surrounding Lakota and Dakota cultural heritage, and suggest that examining such "conflicts of interests" within and between elite assemblages, within the legal production of space, can elucidate controversies over industrial expansion's socio‐environmental threats.